Mean apical concentration and duration in the comparative bioavailability of slowly absorbed and eliminated drug preparations - Pollak, P T; Freeman, D J; Carruthers, S G (Journal of pharmaceutical sciences, 1988)
Present criteria for comparing bioavailability are inadequate when the Cmax and tmax cannot be reliably identified in individual subjects. Drug formulations which are slowly absorbed and eliminated have concentration-time profiles with a broad apex, increasing the likelihood that samples taken at the apical region of the curve will have statistically indistinguishable concentrations. Using data from a study of three dosage forms of piroxicam, we propose an alternative approach which decreases the influence of sampling bias and analytical error on the identification of the apex of the concentration-time curve and provides a simple tool for describing the shape of the curve around the apex. An adequate frequency of sampling around the expected apex of the concentration-time curve and consideration of the coefficient of variation (CV) of the analytical assay when assessing the observed Cmax are used in defining new parameters. This approach may be useful for studying the relationship of onset and duration of maximal plasma concentration to the efficacy and toxicity of drugs and in developing standards for comparing the bioavailability of slow-release preparations, which is of increasing interest to pharmaceutical companies and regulatory agencies.